A multimodal group-based immersive virtual reality intervention for improving cognition and mental health in patients with post-covid-19 condition. A quasi-experimental design study - Cano, Neus; Gómez-Hernández, Josep; Ariza, Mar; Mora, Toni; Roche, David; Porras-Garcia, Bruno; Garolera, Maite (Frontiers in Psychology, 2024)
Introduction: Adults with Post-COVID-19 Condition (PCC) may show cognitive impairments in attention, processing speed, memory, and executive function. Multimodal programs that combine cognitive training, physical activity and emotional tasks, such as mindfulness-based interventions (MBIs), may offer a suitable alternative for improving PCC treatments. Immersive Virtual Reality (IVR) is a promising technology that can enhance traditional cognitive training, physical activity, and MBIs. The current study evaluated the impact of a multimodal IVR intervention, comparing this with a usual care intervention (control group), in order to assess changes in cognition and mental health in adults with PCC. We also aimed to assess user experience factors such as enjoyment, perceived improvement, and fatigue. Method: Thirty-one participants with PCC symptoms were assigned to either the experimental group (IVR, n=15) or the control group (usual care intervention, n=16) in a quasi-experimental design study. The multimodal IVR intervention consisted of MBI, cognitive training and physical exercise and was delivered in a 60-minute group session with 5 participants, twice a week, for 8 weeks (16 sessions in total). Measures of global cognition, attention, processing speed, verbal episodic memory and subjective memory complaints (primary measures), and depressive and anxiety symptoms and fatigue (secondary measures) were assessed at baseline and also after 8 weeks (post-intervention). Results: Mixed between-group (group) and within-group (pre-post assessments) ANOVAs revealed significant group*time interactions in global cognition, simple attention, processing speed, memory and depressive symptoms, with large effect sizes. There was also a marginally significant group*time interaction for executive function. Follow-up analyses comparing pre-and post-intervention outcomes for each group separately showed that the experimental group significantly improved in global cognition, processing speed, memory and depressive symptoms, while the control group showed no significant pre-post changes. Friedman tests showed a significant main effect of time, with a gradual increase in enjoyment over the intervention. In addition, perceived improvement scores remained high throughout the intervention, and patient reported fatigue levels did not fluctuate significantly. Conclusions: Despite their inherent limitations, our findings mark a pioneering step towards improving cognition and mental health outcomes in PCC through the innovative use of new technology and a VR-based multimodal intervention.